A study of reading strategies and effects of reading ability levels and text types on rational deletion cloze test performance of first year law students at Khon Kaen University - Nantawan Senchantichai (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2010